STOCKS OF MACROTOMY COLORING – MACROTOMIA EUCHROMA (Royle) Pauls. AND THE IMMORTELLE OF SAMARKAND - HELICHRYSUM MARACANDICUM Popov ex Kirp. IN JALAL-ABAD AND NARYN REGIONS OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the article of the natural populations of the Jalal-Abad and Naryn regions, thereserves of the dye macrotomy - Macrotomia euchroma (Royle) Pauls were first determined. Andthe immortality of Samarkand - Helichrysum maracandicum Popov Ex Kirp. Studies on biologicaland operational reserves of two types were conducted, distribution areas and annual billet limitswere compiled. The area of macrotomy of coloring in the Jalal-Abad region is 42.5 hectares witha total biological supply of roots of 33.39 tons in dry form. Operational supply - 16.7 tons. In theNaryn region, the macrotomy of coloring on an area of 1585 hectares was established. The biological reserve is 739.6 tons, operational - 369.8 tons. The habitat of the immortality of Samarkandin the Chatkal Valley of the Zalal -Abad region, suitable for harvesting drug raw materials, isestimated at 1000 hectares, where the biological supply of dry inflorescences is 150 tons, and theoperational - 100 tons .
Keywords: medicinal plants, dyeing macrotomy, Samarkand Immorter, stocks, areas, limits, raw materials.